Pattern of organisms causing central nervous system shunt related infections and their antibiotic susceptibility profile in a tertiary care setup - Irfan, Rafia; Mirza , Irfan Ali; Zaman, Gohar; Zulfiqar, Azka; Qamar, Uzma; Sajjad, Zunera (Infectious Diseases Journal of Pakistan, 2023)
Background: Central nervous system (CNS) shunt-associated infections pose a significant threat, necessitating an in-depth understanding of the frequency and antimicrobial sensitivity patterns of the implicated pathogens. This research aimed to ascertain the frequency and antimicrobial sensitivity patterns of pathogens isolated from central nervous system shunt associated infections. Material and Methods: This cross-sectional study was conducted from April to September 2020 at the Neurosurgical department of Combined Military Hospital, Rawalpindi, and the Department of Microbiology, Armed Forces Institute of Pathology. 95 cerebrospinal fluid samples obtained through direct aspiration. The study employed standard microbiological techniques for pathogen isolation, identification, and antimicrobial susceptibility testing following CLSI guidelines 2019. Results: Pathogens isolated from central nervous system shunt associated infections included Staphylococcus spp. (29.47%), Escherichia coli (16.84%), Acinetobacter baumannii (13.68%), Klebsiella pneumoniae (10.53%), Pseudomonas spp. (8.42%), Enterococcus spp. (7.37%), Morganella morganii, Enterobacter cloacae, and Candida spp. (2.11% each), Stenotrophomonas maltophila (1.05%), and mixed infections. Among Gram-negative pathogens, 95% were susceptible to Polymixin B, 93% to Meropenem, and 55% to Cefepime. All Gram-positive organisms were sensitive to Vancomycin and Linezolid (100%). Conclusion: Escherichia coli, Acinetobacter baumannii, Klebsiella pneumoniae, and Pseudomonas aeruginosa were prevalent Gram-negative rods in infections related to CNS shunts, with Staphylococcus spp. following. Gram-negative bacteria exhibited sensitivity to Polymixin B, Meropenem, and Cefepime, while Gram-positive organisms were responsive to Vancomycin and Linezolid. The significant occurrence of Gram-negative rods emphasizes their consideration in empirical antimicrobial therapy recommendations for minimizing death and disability. Keywords: Shunt-associated infections of central nervous system, Antibiotic sensitivity, Gram Negative Rods, Meropenem